Explaining Cross-National Variation in Workplace Employee Representation - John Forth; Alex Bryson; Anitha George (Institute for the Study of Labor (IZA), 2016)
Across Europe, there are many differing opinions on whether workplace employee representation should be encouraged or discouraged. Yet there is very little evidence on the variations in workplace employee representation across Europe or the reasons for this. We use a workplace survey covering 27 EU countries to show that its incidence is strongly and independently correlated with the degree of centralization in a country's industrial relations regime and the extent of legislative support. Industry rents are also important in explaining trade union presence, but are unimportant in the case of works councils. Turning to the effects of workplace employee representation, we find support for the exit-voice model – traditionally associated with Anglo-Saxon regimes – whereby worker representation is associated with poorer perceptions of the employment relations climate and with lower voluntary quit rates.
Keywords: J51; J53; J83; 330; trade unions; works councils; employee representation; social dialogue